Value creation : the definitive guide for business leaders - Mahajan, Gautam, 1946- (SAGE Publications India Pvt Ltd, 2016)
Increasing disruption, diminishing returns, and demanding Customers require business leaders to create more Value, remain relevant, and stay ahead of competition. CEOs have to evolve a "Value Creation" culture for the company so as to properly balance the interests of Customers, Employees, Investors, and the Marketplace.